Research report: South African commercial real estate as an inflation hedge - Taderera, Marimo (My University, 2019)
One of the primary objectives of any investment manager is to protect investors’ wealth against the negative effects of inflation. Real estate investments have traditionally been viewed as a good inflation hedge. Property has been included in mixed asset portfolios for two main reasons, the first being for diversification benefits, the second being for its alleged inflation hedging benefits. Escalation clauses in lease agreements and rent reviews are the mechanisms through which investors adjust rentals for inflation, and do not necessarily allow investors to adjust rentals for inflation instantaneously. The purpose of this study is to investigate the inflation hedging ability of South African Commercial Real Estate investments (CRE) and employs quantitative techniques to study the relationship between Inflation rates and CRE returns. The Vector Error Correction (VEC) model for cointegrated time series was used to investigate the long run relationship between property returns and inflation. This study finds that retail and industrial property hedge against inflation in the long-run, with retail property being the better inflation hedge of the two property types
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfillment of the requirements of the degree of Master of Science in Building. Johannesburg, June 2019
Keywords: Real estate investment--South Africa; Commercial real estate--South Africa; Real estate development